Characterization and comparative sequence analysis of replication origins from three large Bacillus thuringiensis plasmids. - Baum, J A (1991)
The replication origins of three large Bacillus thuringiensis plasmids, derived from B. thuringiensis HD263 subsp. kurstaki, have been cloned in Escherichia coli and sequenced. The replication origins, designated ori 43, ori 44, and ori 60, were isolated from plasmids of 43, 44, and 60 MDa, respectively. Each cloned replication origin exhibits incompatibility with the resident B. thuringiensis plasmid from which it was derived. Recombinant plasmids containing the three replication origins varied in their ability to transform strains of B. thuringiensis, Bacillus megaterium, and Bacillus subtilis. Analysis of the derived nucleotide and amino acid sequences indicates that the replication origins are nonhomologous, implying independent derivations. No significant homology was found to published sequences of replication origins derived from the single-stranded DNA plasmids of gram-positive bacteria, and shuttle vectors containing the three replication origins do not appear to generate single-stranded DNA intermediates in B. thuringiensis. The replication origin regions of the large plasmids are each characterized by a single open reading frame whose product is essential for replication in B. thuringiensis. The putative replication protein of ori 60 exhibits partial homology to the RepA protein of the Bacillus stearothermophilus plasmid pTB19. The putative replication protein of ori 43 exhibits weak but extensive homology to the replication proteins of several streptococcal plasmids, including the open reading frame E replication protein of the conjugative plasmid pAM beta 1. The nucleotide sequence of ori 44 and the amino acid sequence of its putative replication protein appear to be nonhomologous to other published replication origin sequences.